Diagnóstico situacional de la Compañía ARMEVIZA CIA.LTDA. Pujilí. - Quintana Hoyos, María José (2021)
The situational diagnosis allows to identify the state in which a company is, taking into account internal and external factors; in order to present in the future, the possible alternatives of improvement and to take right decisions in that respect. The research that is presented had as a general objective: To elaborate an institutional diagnosis oriented to the improvement of the administrative management of the Medycin Specialties Clinic. The methodology is based on a qualitative approach, with support in some techniques of descriptive statistics from the quantitative perspective, the type of research was descriptive-explicative, and the documentary design with support in field or in situ techniques, which allowed obtaining information both from files, reports, and data taken from reality through the application of structured interviews both to the Directors and to the total staff working in the Medycin Specialties Clinic. This set of techniques and instruments showed that the company has weaknesses in the administrative, financial and human talent processes that must be corrected, among them the absence of a manual of functions and processes, the absence of an integral administrative system, the lack of an organizational structure, which implies a disorientation in the personnel. The researcher through the situational diagnosis proposes to correct such problems to contribute to the achievement of the strategic objectives of market and reinvestment